Analisis Belanja Daerah dalam Pemerataan Tenaga Kesehatan di Puskesmas - Ismoyo, Muhammad Bayu (Ministry of Home Affairs, 2023)
Health workers are a key factor in determining the quality of health development. Puskesmas (Community Health Center), as the first line of health care facility (FKTP), has an important role in providing health care services. However, the provision of health workers for Puskesmas is not optimal despite the receiving stimulation received in the form of from financial support and regional authority. This study aimed to present the process of regional expenditure for the provision of health workers and to explore the potential factors in the financing policy in of Puskesmas. The study uses used a qualitative approach with a meta-analysis method based on the results of a literature study. The results of the study indicated 3 contributing factors, including: 1) Disproportionality inaccuracy of the health worker plan curement; 2) The dominance of personnel expenditure; and 3) Refocussed Reallocation of health budget due to the COVID-19 pandemic.